Exploring the Mechanism of Cr(VI) Catalyzed Hypochlorous Acid Decomposition. Issue 15 (24th March 2022) - Busch, Michael; Simic, Nina; Ahlberg, Elisabet
Abstract: Chlorate is produced through electrolysis of a chloride containing electrolyte in an undivided cell. Cr(VI) is added to the electrolyte in order to minimize the amount of oxygen formed through the homogeneous decomposition of hypochlorite. Despite the importance of Cr(VI) for the chlorate process we posses only very limited knowledge regarding the active Cr(VI) species and mechanisms through which it aids chlorate formation and inhibits O2 evolution. Using density functional theory (DFT) modeling we present for the first time a detailed reaction mechanism for the chromate catalyzed chlorate formation. Our calculations indicate, that the reaction is initialized by the formation of a Cr(VI)‐O−ClOCl species which forms Cr(VI)‐OClO intermediate. This step is found to be rate determining with a rate constant which is comparable to the disproportionation reaction without catalyst. Chlorate is then obtained either through an uncatalyzed oxidation of chlorite to chlorate or the nucleophilic attack of OCl − followed by a second Cl − elimination step. The comparison of the activity of the different Cr(VI) species reveals that only CrO4 2− is active whereas HCrO4 − and Cr2 O7 2− display sluggish kinetics. Abstract : Making Chlorate . A full mechanism for the industrially important Cr(VI) catalyzed oxidation of HOCl to chlorate is described. Based on this mechanism CrO4 2− is identified as active species.